When Citizenship Meets Consumption: Measuring Customer Experience Quality in For-Profit Public Services - Medimagh, Safa; Triki, Abdelfattah (Revue Internationale des Sciences de Gestion, 2025)
In liberalized markets, state-owned enterprises (SOEs) face a dual reality—rewarding their public mission while competing with private firms. Therefore, SOEs must balance public service mandates with commercial competition. Existing customer experience (CX) scales, designed for the private sector, fail to capture the unique drivers of CX in these hybrid SOEs. This study develops and validates a multidimensional scale, EXQ-PUB, to address this gap. Grounded in service-dominant logic and the resource-based view, it introduces a novel dimension, Economic Patriotism, reflecting customers’ symbolic attachment to national institutions. A sequential mixed-methods approach—using laddering interviews and two surveys with Tunisie Telecom customers—confirmed a four-dimensional, second-order formative structure: Economic Patriotism, Peace of Mind, Outcome Focus, and Product Value. PLS-SEM analysis revealed that specialized marketing capabilities positively influence EXQ-PUB, which in turn drives attitudinal and behavioral loyalty, fully mediating this relationship. The findings show that CX in public services is profoundly shaped by socio-symbolic motivations, extending CX theory to public-private contexts and providing managers a diagnostic tool for enhancing competitiveness and trust.